CMM-Based Volumetric Assessment Methodology for Polyethylene Tibial Knee Inserts in Total Knee Replacement - Wei Jiang; Cuicui Ji; Zhongmin Jin; Yuntian Dai (Applied Bionics and Biomechanics)
Total knee replacement is a common surgical procedure in orthopaedics. Accurate volumetric wear assessment of the polyethylene knee inserts has been an essential subject for improving the longevity. A new CMM-based methodology was presented to determine volumetric material loss based on curve surface fitting without prewear data, CAD model, or original design of drawings. Both computational and experimental simulated volume removal tests were run to validate the methodology by comparing with the gravimetric measurements. The volume and linear wear of the tibial inserts were calculated using the presented method based on the coordinates acquired by the CMM. The results indicate that the methodology is adequate for clinically retrieved tibial inserts where no prewear data are provided. This technique can also be used for biotribological study of other polyethylene components, since wear and damage can be assessed visually and volumetrically.